2004
DOI: 10.1080/00049158.2004.10674932
|View full text |Cite
|
Sign up to set email alerts
|

Feeding preferences of the Christmas beetleAnoplognathus chloropyrus(Coleoptera: Scarabaeidae) and four paropsine species (Coleoptera: Chrysomelidae) on selectedEucalyptus grandisclonal foliage

Abstract: Christmas beetles (Coleoptera: Scarabaeidae) (Anoplognathus spp.) and paropsine leaf beetles (Coleoptera: Chrysomelidae) are common defoliators of eucalypts, including several important plantation species, throughout south-eastern Australia. It has already been demonstrated that populations and individuals of several eucalypt species vary in susceptibility to defoliation by these leaf-chewing beetles. The objective of this study was to determine whether significant variation in resistance to insect herbivory w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…These include stem-feeders (Abbott, 1993) such as African black beetle (Paine et al, 2011) and common defoliators such as the Christmas beetles ( Anoplognathus spp.) (Johns et al, 2004). It has been suggested that the use of fertilizer with nitrogen (N) in eucalypt plantations could be used as a management option as it has been found to either moderate or negate the effect of severe insect defoliation on growth (Pinkard et al, 2006a).…”
Section: Control Methodsmentioning
confidence: 99%
“…These include stem-feeders (Abbott, 1993) such as African black beetle (Paine et al, 2011) and common defoliators such as the Christmas beetles ( Anoplognathus spp.) (Johns et al, 2004). It has been suggested that the use of fertilizer with nitrogen (N) in eucalypt plantations could be used as a management option as it has been found to either moderate or negate the effect of severe insect defoliation on growth (Pinkard et al, 2006a).…”
Section: Control Methodsmentioning
confidence: 99%
“…Sample sizes (the number of trees from each population) are shown next to each bar resistant E. grandis clones were no higher in 1,8-cineole concentration than susceptible clones(Johns et al 2004). Furthermore, experiments manipulating the concentration of both 1,8-cineole and sideroxylonal in leaves have suggested that FPCs have a larger effect on Christmas beetles…”
mentioning
confidence: 99%
“…The feeding preference of L. femoratus adult suggest that this insect may be classified as monophagous, since phytochemical characteristics are common among species of Arecaceae (Asmussen et al 2006;Bjorholm et al 2006). The phenology and physiology of young palms before the reproductive phase is affected by the damage caused by L. femoratus; secondary compounds derived from plants injuries have important effects on herbivores, and in many cases, act as attractants and phago-stimulants (Vallejo et al 1998;Johns et al 2004;Diagne et al 2006).…”
Section: Discussionmentioning
confidence: 99%